Aplicativo mattics para mejorar el proceso de aprendizaje en matemáticas de los estudiantes con discalculia de la EEB Benjamín Rosales Aspiazu, Pimocha - Babahoyo - Flores Martinez, Cyndi Xiomara (2023)
The main objective of this research work is to propose the MatTics Application to improve the learning process in mathematics of students with dyscalculia from the EEB Benjamín Rosales Aspiazu, Pimocha - Babahoyo. In the research, the deductive method was used, with the observation technique and the survey of 38 students from second to seventh of the “Benjamín Rosales Aspiazu” Basic Education School, Pimocha-Babahoyo. The content of the software is based on the mathematics curriculum provided by the Ministry of Education, for the development of the system the needs of the students and teachers in charge of teaching classes were mainly considered Propose the MatTics Application to improve the learning process in mathematics of students with dyscalculia from the EEB Benjamín Rosales Aspiazu, Pimocha - Babahoyo. Keywords: Educational software, learning, technological resources, Applicative, discalculia.